Profesionalisme Guru dalam Upaya Peningkatan Mutu Pendidikan Islam di Era Globalisasi - Muflikhatul Munawaroh (Al-Fikr: Jurnal Pendidikan Islam, 2021)
Indonesia is currently experiencing an education crisis. Education is the key to the success of a nation. Human Resource Improvement is an outstanding problem solving solution. Teachers as educational staff and the main factor in the creation of a qualified Islamic education. Teacher professionalism has an effect on improving the quality of education. This study uses a qualitative approach with library research research methods in the form of documents. The data analysis technique used was descriptive (non-statistical) analysis technique. The results of the study: First, teacher professionalism in improving the quality of Islamic education can be seen from four aspects of competence, namely pedagogical competence, personality competence, social competence, and professional competence. Second, the supporting factors are divided into two, namely internal factors and external factors while the inhibiting factors, namely the majority of teachers have not fully pursued their profession, there are still universities that produce original teacher graduates, and the low motivation of teachers in improving the quality of the profession. Third, the impact of the low professional competence of teachers is that learning activities are less effective and efficient, learning is less than optimal, the learning atmosphere is less pleasant and comfortable, learning outcomes are less creative, active, and productive.